2021
DOI: 10.1111/pan.14063
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative anaphylaxis in children: A report from the Wake‐Up Safe collaborative

Abstract: Background Anaphylactic reactions to antigens in the perioperative environment are uncommon, but they have a potential to lead to serious morbidity and/or mortality. The incidence of anaphylactic reactions is 1:37 000 pediatric anesthetics, and substantially less than the 1:10 000 to 1:20 000 incidence in the adult population. Neuromuscular blocking agents, latex, and antibiotics are the most frequently cited triggers. To date, there is no comprehensive report on perioperative anaphylactic reactions in childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
10

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 21 publications
0
13
0
10
Order By: Relevance
“…24,25 TA B L E 3 Changes in acid-base, electrolyte, and hemoglobin concentrations during infusion of modified fluid gelatin 4% in saline (sal-GEL) or in a balanced electrolyte solution (bal-GEL). The data are presented as mean ± SD (95%CI) Generally, the incidence of perioperative anaphylactic reactions is lower in children (1:37 000) than in adults (1:10 000-1:20 000), 26 and lowest in neonates and infants. 27 Neuromuscular blocking agents, latex, and antibiotics are the most frequently cited triggers.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 TA B L E 3 Changes in acid-base, electrolyte, and hemoglobin concentrations during infusion of modified fluid gelatin 4% in saline (sal-GEL) or in a balanced electrolyte solution (bal-GEL). The data are presented as mean ± SD (95%CI) Generally, the incidence of perioperative anaphylactic reactions is lower in children (1:37 000) than in adults (1:10 000-1:20 000), 26 and lowest in neonates and infants. 27 Neuromuscular blocking agents, latex, and antibiotics are the most frequently cited triggers.…”
Section: Discussionmentioning
confidence: 99%
“…It is based on specific components: (1) 'smart aims' defined in advance as the goal(s) for the program; (2) 'key drivers', that is factors required to support the program (e.g., financial and human resources, knowledge dissemination and institutional leadership support for implementation of QI initiatives) and lastly (3) interventions performed to make the key drivers fully operational. Since its development almost a decade ago, the Wake Up Safe Collaboration has contributed with reports on multiple relations of high importance for the quality in pediatric anesthesia [16][17][18][19]. The latest being a report on perioperative anaphylaxis in children published early in 2021 [19].…”
Section: Quality Improvement In Pediatric Anesthesiamentioning
confidence: 99%
“…Since its development almost a decade ago, the Wake Up Safe Collaboration has contributed with reports on multiple relations of high importance for the quality in pediatric anesthesia [16][17][18][19]. The latest being a report on perioperative anaphylaxis in children published early in 2021 [19]. Overall, the analysis of reason for and preventability of adverse events is considered a great strength of the Collaboration.…”
Section: Quality Improvement In Pediatric Anesthesiamentioning
confidence: 99%
“…The adoption of a latex‐free environment in most countries has eliminated sensitivity to latex and subsequently decreased anaphylaxis to this agent. A review using the Wake‐Up Safe database recently identified antibiotics, neuromuscular blocking agents, chlorhexidine, and dyes used for radiologic imaging as the most common agents responsible for allergic reactions in pediatric‐aged patients 7 . Of the neuromuscular blocking agents, rocuronium and succinylcholine are the most common.…”
Section: Introductionmentioning
confidence: 99%
“…A review using the Wake-Up Safe database recently identified antibiotics, neuromuscular blocking agents, chlorhexidine, and dyes used for radiologic imaging as the most common agents responsible for allergic reactions in pediatric-aged patients. 7 Of the neuromuscular blocking agents, rocuronium and succinylcholine are the most common. Sugammadex (Bridion ® , Merck & Co.) is a novel pharmacologic agent that received approval for clinical use from the United States Food & Drug Administration (FDA) in December 2015.…”
Section: Introductionmentioning
confidence: 99%